The Resurgence of Religion in America’s Prisons - Hallett, Michael A. (Religions, 2014)
This article discusses the growing prominence of “faith-based” programs in American corrections and the historical context of penal regime change during periods of economic crisis. The article traces areas of overlap and divergence in recent discussions of penal reform in the U.S. The article suggests a new American penitentiary movement is emerging, noting central tenets of faith-based programs have salience for both conservatives and liberals: on the one hand, faith-based programs are largely paid for by church congregations and volunteers, which appeals to conservatives’ desire to shrink government and get taxpayers out of the business of community building; on the other, faith-based programs demonstrate a recommitment to having at least some level of programming in prisons, which satisfies the left’s view that community building and social capital ultimately lower recidivism. The paper documents several prominent faith-based correctional programs while articulating an agenda for research.